Distributed source coding for utilization of inter/intra source correlation - Mo, Hong; Chen, Jianhua; Lang, Xun; Li, Jingjian (Signal processing. Image communication, 2022)
In many practical distributed source coding (DSC) applications, correlation information plays several important roles at decoding, which provides the prior knowledge of the source statistics for the decoding algorithms to start work. Therefore, the accurate utilization of such correlation information has a significant impact on decoding performance. In this work, a hybrid DSC (HYDSC) scheme is proposed to generate the “soft” information about the clean source symbols, which allows the channel code-based DSC scheme to effectively utilize the inter/intra source correlation without requiring prior knowledge of its statistics, so as to further improve the decoding performance. Further performance improvement, at the cost of moderate increasing in computational complexity, can be achieved by performing additional iterations on the basis of the HYDSC scheme. We mainly focus on, in particular, applications where Slepian–Wolf coding and usual source coding are jointly used to exploit both the correlation among the adjoining source symbols and the correlation between the sources. Experiment results indicate that the presented scheme not only show superior performance from an error correction viewpoint, but also achieve better compression ratio in the case of strong internal correlation of the source sequence, as compared with the previous DSC techniques. •Analyze the limitations of source code-based and channel code-based DSC schemes.•More accurate “soft” information about the source symbols is generated.•The proposed scheme allows the channel code-based DSC scheme to effectively utilize the inter/intra source correlation.•The scheme shows superior error correction and compression performance.